Performance in the City - PLANE SITE (urbanNext, 2018)
Aside from the provision of music concerts, a concert hall as was the case with Wroclaw s National Forum of Music also catalyzes urban changes. Culture goes beyond entertainment: it is woven into the fabric of a city s identity, providing opportunities for social transformation. Can thoughtful and high-quality scenography play a role in a city s social or educational evolution? And how can the design of an interior space spill out into the city at-large?
Audio&visual, Designing Matter, Energy and sustainability, expanding design practices, No Density, PLANE SITE, Technology and fabrication, Urban Paradigms
Acoustics, Active Building, Active Public Spaces, Aluminum skin, Architecture s challenge, Architecture&art, Audiovisual, Built environment, Cultural agitator, Culture, Design process, Empowering society, Fluid space, France, Glass, Glass panels, Iceland, Inspiration, Multifunctional building, Multifunctional space, Music, Paris, Poland, Public buildings, Public Space, Reykjavík, Space & Sound, Sustainability, Sustainable infrastructure, Technology, Urban catalyst, Wroclaw
Keywords: Architecture; Wroclaw s National Forum of Music; Cultural Center; Scenography